Impact of sodium chloride replacement by salt substitutes on the proteolysis and rheological properties of dry fermented sausages. (April 2015) - dos Santos, Bibiana A.; Campagnol, Paulo C.B.; Cavalcanti, Rodrigo N.; Pacheco, Maria T.B.; Netto, Flávia M.; Motta, Eliana M.P.; Celeguini, Renata M.S.; Wagner, Roger; Pollonio, Marise A.R.
Highlights: KCl and CaCl2 did not cause changes in the myofibrillar proteins. CaCl2 decreased the degradation of sarcoplasmic proteins. KCl decreased the sample firmness. CaCl2 increased the hardness of the samples. CaCl2 decreased the firmness of the samples over storage time. Abstract: The effect of a 50% reduction of NaCl and its replacement by KCl, CaCl2, and a blend of KCl and CaCl2 (1:1) on the proteolysis and rheological properties of dry fermented sausages was investigated. The reduction or replacement of NaCl by KCl did not cause changes in the electrophoretic profile and the addition of CaCl2 decreased the degradation of sarcoplasmic proteins during the manufacturing process. Samples with a 50% reduction of NaCl showed a higher content of the amino acids Arg, Glu, His, Val, Cys, Lys, and Trp, whereas the samples containing CaCl2 had a higher content of the amino acids Asp, Thr, Ala, Met, Leu, Ile, and Phe. The reduction or replacement of NaCl by KCl decreased sample firmness, whereas the addition of CaCl2 increased the hardness of the samples.